2011
DOI: 10.4322/floram.2011.018
|View full text |Cite
|
Sign up to set email alerts
|

Resistência Natural de Eucalyptus urophylla e Corymbia citriodora à Coptotermes gestroi (Isoptera; Rhinotermitidae) em laboratório

Abstract: Este trabalho teve como objetivo avaliar a resistência natural da madeira de Eucalyptus urophylla e Corymbia citriodora ao ataque de Coptotermes gestroi. A avaliação da resistência a cupins foi realizada segundo a norma ASTM D -3345 (American..., 1994). A média de perda de massa do Pinus elliottii foi superior à do Eucalyptus urophylla e Corymbia citriodora, indicando maior susceptibilidade à ação de Coptotermes gestroi. A superior mortalidade dos cupins, observada em Eucalyptus urophylla e Corymbia citriodora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…These results can be associated with the chemical composition of wood, because those that presented higher wear grades have higher natural extractive contents. As reported by several authors (Supriana, 1985;Rodrigues & Brito, 2011;Paes et al, 2013), depending on the type and concentration of these compounds combined with high density, wood may present higher biological resistance. Loureiro et al (1997Loureiro et al ( , 2000 classified Angelim-vermelho (Dinizia excelsa Ducke) wood as of high density (0.83 gcm -3 ), a value lower than that found in this study (1.05 gcm -3 ), and resistant to attack by xylophagous organisms; however, the authors did not identify such organisms.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…These results can be associated with the chemical composition of wood, because those that presented higher wear grades have higher natural extractive contents. As reported by several authors (Supriana, 1985;Rodrigues & Brito, 2011;Paes et al, 2013), depending on the type and concentration of these compounds combined with high density, wood may present higher biological resistance. Loureiro et al (1997Loureiro et al ( , 2000 classified Angelim-vermelho (Dinizia excelsa Ducke) wood as of high density (0.83 gcm -3 ), a value lower than that found in this study (1.05 gcm -3 ), and resistant to attack by xylophagous organisms; however, the authors did not identify such organisms.…”
Section: Resultsmentioning
confidence: 76%
“…However, Paes et al (2007b) assessed seven native, exotic woods and observed no correlation between biological resistance and wood density. Rodrigues & Brito (2011) studied Pinus elliottii, Eucalyptus urophylla, and Corymbia citriodora and verified that Pinus timber presents higher resistance to Coptotermes gestroi; Gonçalves et al (2013) investigated 10 Amazonian species and observed that the higher the density and the lower the extractive and ash contents, the higher the termite mortality; Stallbaun et al (2017) evaluated the resistance of Sclerolobium paniculatum and classified its timber as highly resistant.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…wood (27.98 ± 10.63%) caused by C. formosanus attacks in comparison with C. gestroi (13.85 ± 9.35%), with this difference possibly being a reflection of the size of the foraging caste or of the activity levels between these two species. Rodrigues & Brito (2011) found, under laboratory conditions, that C. gestroi caused weight loss of the P. elliottii test bodies of 3.85%, which was significantly greater than C. citriodora (2.89%) and E. urophylla (2.86%), and considered the density of the wood and the chemical composition of the P. elliottii logs as possible determining factors for greater susceptibility.…”
Section: /10mentioning
confidence: 95%
“…Alguns trabalhos publicados [8][9][10][11][12][13] tiveram como objetivo avaliar a resistência de painéis aglomerados ao ataque de organismos xilófagos (fungos e cupins), mediante o uso de adesivos a base de ureia-formaldeído e ou tanino-formaldeído, apresentando resultados variados em função dos diferentes tratamentos aplicados. Porém, de forma geral, foram satisfatórios.…”
Section: Introductionunclassified